2022
DOI: 10.1371/journal.pone.0271195
|View full text |Cite
|
Sign up to set email alerts
|

Promoting teaching innovation of Chinese public-school teachers by team temporal leadership: The mediation of job autonomy and the moderation of work stress

Abstract: This study examines the impact of team temporal leadership, leaders’ behaviors regarding scheduling, allocating time resources, and coordinating team members, on teachers’ innovative behavior. Questionnaire surveys on 2021 Chinese elementary and secondary public-school teachers show that team temporal leadership exerts a significant positive direct effect on teaching innovation and the effect can be facilitated through the mediation of job autonomy. Moreover, both the direct effect and the second-leg of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
(154 reference statements)
1
2
0
Order By: Relevance
“…When job autonomy in individuals increases, it will reduce the worry in employees by restructuring and increase employee innovation ideas; it will also make employees more freely explore new ideas in their work at a time of stressful circumstances. In line with that, Li & Zhu (2022) found that job autonomy of teachers has a positive relationship with is associated with teaching innovations carried out by teachers in schools.…”
Section: Discussionsupporting
confidence: 63%
“…When job autonomy in individuals increases, it will reduce the worry in employees by restructuring and increase employee innovation ideas; it will also make employees more freely explore new ideas in their work at a time of stressful circumstances. In line with that, Li & Zhu (2022) found that job autonomy of teachers has a positive relationship with is associated with teaching innovations carried out by teachers in schools.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, Innovative behavior plays an important role in improving student performance and school progress which is the concern of a mathematics teacher 28 , 29 . However, this study shows that teachers' innovative behavior is still low and needs attention 2 , 30 . Therefore, studies are needed to theoretically, practically, and significantly increase teachers’ innovative behavior.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Enhancing innovative behavior has emerged as a significant area of focus in the twenty-first century 1 . This behavior is widely acknowledged to yield positive outcomes, benefiting both teacher performance during instruction and student capabilities 2 , 3 . As Docherty 4 argued, the introduction of teacher innovative behavior can greatly optimize the learning process, fostering an environment that is conducive to heightened student engagement.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical study reveals that work stress assessed using the effort-reward imbalance (ERI) ratio would increase the risk of poor periodontal status (Sato et al, 2022). Another recent study reveals that teaching innovation could be higher through promoting temporal leadership but at lower work stress levels (Li & Id, 2022), which indicates that work stress can have an impact on process innovation, particularly in teaching innovation. In the medical field, role stressors for nurses said to be the most important reason behind job dissatisfaction (Iyer & Deshmukh, 2018).…”
Section: Work Stressmentioning
confidence: 99%